Communication Strategy of Facilitators in Independent Housing Stimulant Assistance Program - Didit Setiawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study reveals all stages of the communication strategy by facilitators in community assistance in the Self-help Housing Stimulant Assistance Program (BSPS). Because the number of uninhabitable houses in Indonesia is still quite a lot, especially the location of many residents' houses in the ring of fire route, this research was conducted with a qualitative approach to understand the facilitators in the BSPS Program. Researchers tried to obtain information by interviewing and describing the documentation and then analyzing the data obtained. In analyzing each stage of the communication strategy described above, the researcher uses Laswell's theory, namely looking at the communicator, message, media, communicant and impact aspects. The aim is to find out every detail of the aspect that affects the communication process carried out by the facilitator in the BSPS Program. In carrying out the socialization carried out by the facilitator to the community, especially the beneficiaries, was carried out following the stages of the program, with direct community involvement at each stage as one of the community empowerment activities. However, it had not been supported in terms of the media used by the facilitator, considering that the program audience was low-income and many people. The elderly. This is because the Ministry of Public Works and Public Housing in the BSPS program does not yet have a comprehensive and integrated communication strategy.